The Journey of Social Workers and Development Workers in times of pandemic COVID’ 19 in Tacurong City, Philippines - Robles, Eufemia L. (International Journal of Management and Education in Human Development, 2021)
This paper is a narrative on the experience of Social Workers and Development Workers in Tacurong City, Province of Sultan Kudat, Philippines. It focuses on the implementation of Social Amelioration Program (SAP), one of the interventions in responding the world to experience this pandemic, which started April 2020 when the Department of Health confirmed the local transmission of Corona Virus Disease (COVID ’19) in the Philippines. The Aid to Individual in Crisis Situation (AICS) and Livelihood Assistance Grant (LAG) are the programs under Social Amelioration Program(SAP) to augment the basic and financial needs of heavily affected families by pandemic as well as the livelihood assistance for the economic recovery of the beneficiaries. Food packs distribution were given also to affected families through house to house delivery especially during the community quarantine. The Department of Social Welfare and Development is the lead agency in the implementation of Social Amelioration Program and the Local Government Units-Social Welfare and Development Workers are the main actors in the implementation.